2022
DOI: 10.1021/acsbiomaterials.2c00182
|View full text |Cite
|
Sign up to set email alerts
|

From Static to Dynamic: A Review on the Role of Mucus Heterogeneity in Particle and Microbial Transport

Abstract: Mucus layers (McLs) are on the front line of the human defense system that protect us from foreign abiotic/biotic particles (e.g., airborne virus SARS-CoV-2) and lubricates our organs. Recently, the impact of McLs on human health (e.g., nutrient absorption and drug delivery) and diseases (e.g., infections and cancers) has been studied extensively, yet their mechanisms are still not fully understood due to their high variety among organs and individuals. We characterize these variances as the heterogeneity of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 318 publications
0
6
0
Order By: Relevance
“…Recent advances in drug delivery have demonstrated that coating sub-micrometer latex particles with bioinert polymers such as polyethylene glycol (PEG) promotes particle penetration through mucus [17][18][19] . However, as demonstrated by our previous work 6,20,21 and others 8,9,[22][23][24][25] , the mucus hydrogel is highly heterogeneous with a wide distribution in the network mesh size from tens to hundreds of nanometers; thus, the PEGylated solid particles can still be physically trapped by local small meshes. Decreasing the particle size to ~100nm or less helps circumvent the physical confinement.…”
Section: Table Of Contents Main Textmentioning
confidence: 79%
“…Recent advances in drug delivery have demonstrated that coating sub-micrometer latex particles with bioinert polymers such as polyethylene glycol (PEG) promotes particle penetration through mucus [17][18][19] . However, as demonstrated by our previous work 6,20,21 and others 8,9,[22][23][24][25] , the mucus hydrogel is highly heterogeneous with a wide distribution in the network mesh size from tens to hundreds of nanometers; thus, the PEGylated solid particles can still be physically trapped by local small meshes. Decreasing the particle size to ~100nm or less helps circumvent the physical confinement.…”
Section: Table Of Contents Main Textmentioning
confidence: 79%
“…The porosity range and its variation, as a consequence of a particular disease, have a critical role in the diffusivity of molecules and nanoparticles. Depending on the relative length scale and penetrant-mucus interactions, different scenarios can be encountered during mucus penetration [177,178]. When penetrants are smaller than the pore size of the mucus network, the resistance to their diffusion largely reflects the viscous resistance of water, assuming that no specific interactions occur with mucus constituents [179].…”
Section: Mucus Viscoelasticitymentioning
confidence: 99%
“…Mucus is a soft viscoelastic material that lines the surface of respiratory, reproductive, and gasterointestinal tracts in mammals. In the human body, mucus serves a multitude of crucial functions that include acting as a lubricating agent and serving as a highly selective and permeable barrier to the infiltration and transport of pathogens and particulates to epithelial layers [ 1 , 2 , 3 , 4 , 5 ]. Composed primarily of water (∼90–95%), a primary constituent of mucus is mucin, which is composed of polymeric glycoprotein macromolecules that contribute to its viscoelasticity and stickiness.…”
Section: Introductionmentioning
confidence: 99%
“…Mucus is commonly characterized using macrorheology measurements that allow the determination of bulk, macroscale properties such as shear viscosity, and effective dynamic loss (viscous) and storage (elastic) shear moduli [ 16 , 17 ]. For effective function, these properties need to lie within physiologically determined ranges [ 3 ].…”
Section: Introductionmentioning
confidence: 99%